Exploration of the mechanism of fermented turmeric preventing glucolipid metabolic disorder: Insights into signaling of microbiota-SCFAs-brown adipose tissue axis in mice - Xingliang Xiang; Yukun Liu; Zhaoxiang Zeng; Xueyan Zhao; Qingxin Shi; Xing Huang; Haijun Yang; Chengwu Song; Shunqing Xu; Shuna Jin (Journal of Functional Foods)
Glucolipid metabolic disorder (GMD) is an urgent global public health problem. Fermented turmeric (FT) might be a functional food resource for prevention and treatment of GMD, but its effect and mechanism remain unclear. In this study, the activity of FT on GMD involving brown adipose tissue (BAT) was investigated. The results of animal experiment suggested that 4-week FT supplement comprehensively improved the characteristic symptoms of GMD, showing better therapeutic efficacy than crude turmeric. Due to activation of BAT in the process of treatment, transcriptome analysis was performed for the underlying mechanism based on BAT. As a result, butanoate metabolism signaling pathway was highlighted with regulating ACSM3 and HADH. Considering the poor absorption of curcuminoids, intestinal environment was analyzed for further exploring the upstream signal of short-chain fatty acids (SCFAs) metabolism. And FT reversed intestinal dysbiosis and enriched SCFAs producing bacteria, including Bacteroides, Odoribacter, Parvibacter and un_Muribaculaceae. Simultaneously, the production and absorption of three SCFAs had been upregulated. Increasing SCFAs could play a crucial role in stimulating butanoate metabolism of BAT to improve GMD, especially butyric acid. Consequently, the SCFAs mediating crosstalk between microbiota and BAT could contribute to anti-GMD activity. Our study demonstrated the great potential of FT for prevention and treatment of GMD, and provided a basis for its further application and development.